Mechanical characterization of polyester / guadua fiber and polyester / guadua-glass fiber - Moreno Montoya, Luis Edgar (Scientia et Technica, 2018)
This work shows the experimental results obtained from the mechanical characterization of polymer matrix composite materials reinforced with guadua fiber and / or glass fiber. The polymeric matrix used was unsaturated polyester resin. The guadua or bamboo fibers were obtained from the guadua angustifolia Kunt species by a mechanical defibering process and later they were subjected to a chemical treatment in sodium hydroxide. The composite material with a constant fiber volume fraction was produced by manual method in the form of a sheet from which standardized specimens were obtained, which in turn were subjected to tensile, bending and Charpy impact tests. The results of the mechanical tests show that in the composite material resulting from mixing guadua fiber with glass fiber in equal proportions, there is an increase in stiffness, tensile strength, impact resistance with respect to composite material with only guadua fiber, but in turn, there is a decrease in ductility and flexural strength.